2012
DOI: 10.1021/jp3059068
|View full text |Cite
|
Sign up to set email alerts
|

One-Electron Oxidation of Neutral Sugar Radicals of 2′-Deoxyguanosine and 2′-Deoxythymidine: A Density Functional Theory (DFT) Study

Abstract: One electron oxidation of neutral sugar radicals has recently been suggested to lead to important intermediates in the DNA damage process culminating in DNA strand breaks. In this work, we investigate sugar radicals in a DNA model system to understand the energetics of sugar radical formation and oxidation. The geometries of neutral sugar radicals C1′•, C2′•, C3′•, C4′• and C5′• of 2′-deoxyguanosine (dG) and 2′-deoxythymidine (dT) were optimized in the gas phase and in solution using the B3LYP and ωB97x functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 89 publications
(169 reference statements)
3
41
0
Order By: Relevance
“…This experimental observation was supported by our calculation of the energy of C2′ + within dGuo sing the ω 97x/6-31++G(d) method with PCM. Our calculation showed that geometry optimization of C2′ + proceeds on a barrierless surface to produce C1′ + by transferring a hydrogen from C1′ to C2′, see Figure 2d in reference Kumar et al, 2012b.…”
Section: Electron Reaction With Dnamentioning
confidence: 82%
See 4 more Smart Citations
“…This experimental observation was supported by our calculation of the energy of C2′ + within dGuo sing the ω 97x/6-31++G(d) method with PCM. Our calculation showed that geometry optimization of C2′ + proceeds on a barrierless surface to produce C1′ + by transferring a hydrogen from C1′ to C2′, see Figure 2d in reference Kumar et al, 2012b.…”
Section: Electron Reaction With Dnamentioning
confidence: 82%
“…The simulated spectrum assumed axial symmetry and employed the following parameters: A ⊥ = 775 G, A || = 610 G, g ⊥ = 2.00, g || = 2.01 and linewidth = 12 G. The origin of these radicals is suggested by the fact that LEEs are known to create strand breaks in DNA by dissociative electron attachment (DEA) (Boudaïffa et al, 2000). Thus, LEE can form both C3′• dephos and ROPO 2 • − by DEA at the sugar phosphate backbone (scheme 2) (Kumar and Sevilla, 2009, 2012; Adhikary et al, 2014a). …”
Section: The Radiation Chemistry Track Structure Of Ion-beam Irradmentioning
confidence: 99%
See 3 more Smart Citations